2016
DOI: 10.1039/c5ta08622a
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced degradation of lead halide perovskite solar cells caused by the hole transport layer/metal electrode interface

Abstract: Photo-induced degradation of PSCs is caused by damage at the HTM/Au interface, which can be recovered by renewal of the Au electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 30 publications
2
84
0
2
Order By: Relevance
“…Song group [ 184 ] proposed a PCE degradation mechanism occurred at HTL/metal electrode interface with light Adv. Energy Mater.…”
Section: Chemical Reactions Between Adjacent Layer Interfacesmentioning
confidence: 99%
“…Song group [ 184 ] proposed a PCE degradation mechanism occurred at HTL/metal electrode interface with light Adv. Energy Mater.…”
Section: Chemical Reactions Between Adjacent Layer Interfacesmentioning
confidence: 99%
“…6, 13 Similarly, stability of complete PSC devices has been investigated with relation to the same environmental factors. 6, [14][15][16][17][18] Interestingly, in addition to the perovskite-related degradation, the stability of the devices was found to greatly depend on device architecture. 17,[19][20][21][22][23][24] This was explained partly by interfacial degradation 19,25 and also by degradation of the charge transporting layers.…”
mentioning
confidence: 99%
“…17,[19][20][21][22][23][24] This was explained partly by interfacial degradation 19,25 and also by degradation of the charge transporting layers. 14,22 Recently, there have been efforts to substitute the widely-used organic Spiro-MeOTAD hole transporting layer (HTL) with inorganic materials to improve the stability of PSCs. 20,21,26 However, it is still unclear what the mechanism increasing the stability is.…”
mentioning
confidence: 99%
“…Organometallic lead halide perovskite (e.g., CH3NH3PbX3 (X=I, Br, Cl)) as light absorber layers plays critical roles in thin film solar cells as reported that the state-of-art perovskite solar cell (PSC) utilizing this kind of material has made extraordinary performance with highest efficiency exceeding 22.1% [1,2]. At present, most of the highly efficient PSCs employ sandwiched architecture of electron transporting layer (ETL)/perovskite absorber/hole transporting layer (HTL), which is initially derived from the solid state dye-sensitized solar cell.…”
Section: Introductionmentioning
confidence: 99%